2006
DOI: 10.1016/j.febslet.2006.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Induction of necrotic cell death and mitochondrial permeabilization by heme binding protein 2/SOUL

Abstract: We found that heme-binding protein 2/SOUL sensitised NIH3T3 cells to cell death induced by A23187 and etoposide, but it did not affect reactive oxygen species formation. In the presence of sub-threshold calcium, recombinant SOUL provoked mitochondrial permeability transition (mPT) in vitro that was inhibited by cyclosporine A (CsA). This effect was verified in vivo by monitoring the dissipation of mitochondrial membrane potential. Flow cytometry analysis showed that SOUL promoted necrotic death in A23187 and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…However, very little information is available about their other biological functions. Previously, we reported that SOUL can facilitate cell death in taxol-and A23187-treated cells (1). Analyzing the protein sequence data base, we found that SOUL contained a sequence with a high similarity to BH3 domains (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, very little information is available about their other biological functions. Previously, we reported that SOUL can facilitate cell death in taxol-and A23187-treated cells (1). Analyzing the protein sequence data base, we found that SOUL contained a sequence with a high similarity to BH3 domains (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…To detect SOUL protein in different types of tissues, we developed anti-SOUL, as was described earlier (1). Using the purified anti-SOUL antibody, different levels of SOUL expression were identified in human tissue samples, and it could be detected in some malignant tissues too (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEBP2 could exaggerate the dissipation of the mitochondrial membrane potential and induce necrosis in concert with calcium (26). This suggested its involvement in intracellular calcium signaling, a process in which ALG-2 is definitely involved as an EF-hand protein.…”
Section: Figure 10 Knockdown Of Endogenous Alg-2 Expression In Hela mentioning
confidence: 99%
“…HEBP2 is highly expressed in the retina and pineal gland (25) and shares 40% sequence similarity with p22 HBP (HEBP1), a ubiquitously expressed heme-binding protein. It has been suggested that HEBP2 plays roles in mitochondrion-mediated cell death (26), which might be related to its ability to interact with the antiapoptotic proteins Bcl-2/Bcl-xl through a BH3-like motif (27,28). Unlike p22 HBP , the ability of HEBP2 to bind heme is controversial, and its roles in heme-related activities, such as the generation of reactive oxygen species, are poorly defined.…”
mentioning
confidence: 99%